Penta-fluorophenol: a Smiles rearrangement-inspired cysteine-selective fluorescent probe for imaging of human glioblastoma. Issue 22 (20th May 2020) - An, Jong Min; Kang, Sangrim; Huh, Eugene; Kim, Yejin; Lee, Dahae; Jo, Hyejung; Joung, Joonyoung F.; Kim, Veronica Jihyun; Lee, Ji Yeoun; Dho, Yun Sik; Jung, Yuna; Hur, Junho K.; et al.
Abstract : A fluorescent molecular probe for the identification of glioblastoma is developed. The probe allows the tracing of the cysteine (Cys) level, which is recognized as a new biomarker of GBM. Abstract : Two of the most critical factors for the survival of glioblastoma (GBM) patients are precision diagnosis and the tracking of treatment progress. At the moment, various sophisticated and specific diagnostic procedures are being used, but there are relatively few simple diagnosis methods. This work introduces a sensing probe based on a turn-on type fluorescence response that can measure the cysteine (Cys) level, which is recognized as a new biomarker of GBM, in human-derived cells and within on-site human clinical biopsy samples. The Cys-initiated chemical reactions of the probe cause a significant fluorescence response with high selectivity, high sensitivity, a fast response time, and a two-photon excitable excitation pathway, which allows the imaging of GBM in both mouse models and human tissue samples. The probe can distinguish the GBM cells and disease sites in clinical samples from individual patients. Besides, the probe has no short or long-term toxicity and immune response. The present findings hold promise for application of the probe to a relatively simple and straightforward following of GBM at clinical sites.